Konektorji v slovničnem opisu znanstvenega besedila - Gorjanc, Vojko (Slavistična revija, 1998)
In the text, connectors connect textual segments of various lenght and they establish correlations between clauses and sentences or between a section of the text and its continuation. They are examined here in a scientific text with respect to their role in the surface construction of the text and in the organization of textual menaning. Moreover, connector correlations are analyzed with respect to the possibility of further development of the text. Classification of the connectors into various morphological-syntactic categories is based on the textological point of view as well.
Keywords: konektorji (ling.); leksikologija; lexicology; skladnja; Slovene; slovenščina; syntax; znanstveni jezik